Definitive radiotherapy for extracranial oligoprogressive metastatic renal cell carcinoma as a strategy to defer systemic therapy escalation. (23rd July 2021) - De, Brian; Venkatesan, Aradhana M.; Msaouel, Pavlos; Ghia, Amol J.; Li, Jing; Yeboa, Debra N.; Nguyen, Quynh‐Nhu; Bishop, Andrew J.; Jonasch, Eric; Shah, Amishi Y.; Campbell, Matthew T.; Wang, Jennifer; et al.
Abstract : Objective: To study whether delivering definitive radiotherapy (RT) to sites of oligoprogression in metastatic renal cell carcinoma (mRCC) enabled deferral of systemic therapy (ST) changes without compromising disease control or survival. Patients and Methods: We identified patients with mRCC who received RT to three or fewer sites of extracranial progressive disease between 2014 and 2019 at a large tertiary cancer centre. Inclusion criteria were: (1) controlled disease for ≥3 months before oligoprogression, (2) all oligoprogression sites treated with a biologically effective dose of ≥100 Gy, and (3) availability of follow‐up imaging. Time‐to‐event end‐points were calculated from the start of RT. Results: A total of 72 patients were identified (median follow‐up 22 months, 95% confidence interval [CI] 19–32 months), with oligoprogressive lesions in lung/mediastinum ( n  = 35), spine ( n  = 30), and non‐spine bone ( n  = 5). The most common systemic therapies before oligoprogression were none ( n  = 33), tyrosine kinase inhibitor ( n  = 23), and immunotherapy ( n  = 13). At 1 year, the local control rate was 96% (95% CI 87–99%); progression‐free survival (PFS), 52% (95% CI 40–63%); and overall survival, 91% (95% CI 82–96%). At oligoprogression, ST was escalated ( n  = 16), maintained ( n  = 49), or discontinued ( n  = 7), with corresponding median (95% CI) PFS intervals of 19.7 (8.2–27.2) months, 10.1 (6.9–13.2) months, and 9.8 (2.4–28.9) months, respectively. Of the 49 patients maintained on the same ST at oligoprogression, 21 did not subsequently have ST escalation. Conclusion: Patients with oligoprogressive mRCC treated with RT had comparable PFS regardless of ST strategy, suggesting that RT may be a viable approach for delaying ST escalation. Randomised controlled trials comparing treatment of oligoprogression with RT vs ST alone are needed.